Fractionated crystallization in semicrystalline polymers. (April 2021) - Sangroniz, Leire; Wang, Bao; Su, Yunlan; Liu, Guoming; Cavallo, Dario; Wang, Dujin; Müller, Alejandro J.
Highlights: FC occurs when a polymer is divided in a large number of microdomains (MDs). When the number of heterogeneities in bulk equals the number of MDs, FC occurs. The injection of nucleating agents or self-nuclei in every MD eliminates FC Nucleation goes from heterogeneous to homogeneous by increasing confinement. Crystallization kinetics can change from sigmoidal to first order by confinement. Abstract: The crystallization of heterogeneously nucleated bulk polymers typically occurs in a single exothermic process, within a narrow temperature range, i.e., a single exothermic peak is detected by differential scanning calorimetry when the material is cooled from the melt. However, when a bulk semicrystalline polymer is subdivided or dispersed into a multitude of totally (or partially) isolated microdomains (e.g., droplets or cylinders), in number comparable to that of commonly available nucleating heterogeneities, several separated crystallization events are typically observed, i.e., fractionated crystallization. This situation is often found for the minor crystallizable component in immiscible blends. When the bulk polymer is dispersed into a number of microdomains that is several orders of magnitude higher than the available number of heterogeneities within it, most microdomains will be heterogeneity-free. In these clean microdomains the nucleation can occur by contact with the interfaces (i.e., surface nucleation) or by homogeneous nucleation inside the microdomain volume. These cases can be easily encountered in cylinders or spheres within strongly segregated block copolymers, or in infiltrated polymers within nanopores of alumina templates. In this work, a comprehensive review of the known cases of fractionated crystallization is provided. The changes upon decreasing microdomain sizes from a dominant single heterogeneous nucleation, through fractionated crystallization, to surface or homogeneous nucleation are critically reviewed. Emphasis is placed on the common features of the phenomenon across the different systems, and thus on the general conclusions that can be drawn from the analysis of representative semicrystalline polymers. The origin of the fractionated crystallization effects and their dramatic consequences on the nucleation and crystallization kinetics of semicrystalline polymers are also discussed. Graphical abstract: Image, graphical abstract